Does Cloud-Based LMS Promote Engaging and Enjoyable Learning? Evidence from High School Accounting Education - Santoso, Jarot Tri Bowo; Octavianto, Said Nur; Ventayen, Randy Joy Magno (Jurnal Pendidikan Progresif, 2025)
Does Cloud-Based LMS Promote Engaging and Enjoyable Learning? Evidence from High School Accounting Education. Accounting is perceived as one of the most difficult subjects among many secondary school students. This problem may arise from the lack of student involvement in learning on the one hand, and from teachers’ use of non-interactive teaching practices on the other. This study bridges the learning gap by using LMS-based Web Cloud Computing media in accounting as a fun and effective learning medium to improve students’ learning outcomes. Objective:  This study aims to enhance learning outcomes by creating a fun learning environment by stimulating student participation through LMS-based web cloud computing media. Methods: Quantitative method with quasi-experimental research design with experimental and control classes in grade XII-SMA N 14, Semarang City. Data were gathered through pre- and post-tests to find out the improvement and effectiveness of learning outcomes. A survey was administered to determine whether the media used were acceptable to the students. The data were analyzed using Independent Samples t-tests, Paired Samples t-test, and N-Gain Test. Results: The findings show that the Learning Management System (LMS) web-based cloud computing platform was perceived as a fun virtual learning medium for learning accounting. The findings demonstrate that over 80% of respondents were strong supporters of all indicators, including the idea that LMS-based cloud computing web media is a fun medium. Conclusion: the cloud-based LMS is effective in enhancing students’ accounting learning achievement, at a moderate level.  The article contributes to theory development by providing a framework for the rational and empirical use of LMS-supported web cloud media computing.  Practical implications: This study offers practical guidance for educators seeking to create meaningful, interactive, and applicable learning media that support student learning outcomes. Keywords: cloud computing, web, learning management system, fun learning media, learning outcomes.